Abstract 15936: Prospective Evaluation of Anti-Ro Pregnancies Supports the Utility of Ambulatory Fetal Heart Rate Monitoring in Detecting Fetal Atrioventricular Block - Cuneo, Bettina F; Abuhamad, Alfred; Copel, Joshua; Cumbermack, Kristopher; Doan, Tam; Donofrio, Mary T; Gropler, Melanie; Haxel, Caitlin; Hogan, Whitnee; Howley, Lisa; Joffe, Gary; Kaplinski, Michelle; et al. (Circulation (New York, N.Y.), 2023)
Introduction:: The management of anti-Ro/SSA positive pregnancies is challenging because fetal atrioventricular (AV) block is rare and fetal echo seldom detects reversible injury. Hypothesis: We hypothesized that ambulatory fetal heart rate/rhythm monitoring improves detection of fetal AV block when compared with echo. Methods: Anti-Ro antibody subjects from 21 US centers at less than 20 weeks of gestation were risk stratified into high and low anti-Ro60 and 52 titers at the New York University (NYU) core laboratory. Low titer was defined by previous NYU data demonstrating no fetal AV block in subjects with anti-Ro60 and 52 less than 1000 arbitrary units per mL. High titer subjects performed 3x/day fetal heart rate/rhythm monitoring and underwent weekly or bi-weekly surveillance fetal echos at 18-26 weeks of gestation. Low titer subjects underwent site-specific surveillance. Abnormal fetal heart rate/rhythm monitoring prompted urgent diagnostic fetal echo. All infants received electrocardiograms. Results: We enrolled 405 subjects (fig). None of the 150 (37%) low titer subjects developed fetal AV block. Of 255 high titer subjects, 241 completed surveillance. High titer subjects monitored 44,187 times; 37 (0.08% ) monitoring episodes were deemed abnormal. Urgent fetal echos of the 37 diagnosed 9 with fetal AV block (7 with 2° AV block), 14 with atrial ectopy and 14 with normal rhythms. No fetal AV block, endocardial fibroelastosis or cardiac dysfunction was detected in the 871 surveillance fetal echoes of high titer subjects following normal FHRM. No fetus developed AV block after the surveillance period; one baby had transient prolonged PR interval, which resolved spontaneously. Conclusions: This prospective study suggests that ambulatory fetal heart rate/rhythm FHRM is superior to echo surveillance for fetal AV block, and antibody titers are useful in risk stratification of anti-Ro positive pregnancies.